Determination of the Probability Distribution of the Mean Sound Level - BATKO, Wojciech; PRZYSUCHA, Bartosz (Archives of Acoustics, 2010)
Assessment of several noise indicators are determined by the logarithmic mean Lmean=Sn10log((1/n)Σi=1n 100.1Li), from the sum of independent random results L1, L2, ..., Ln of the sound level, being under testing. The estimation of uncertainty of such averaging requires knowledge of probability distribution of the function form of their calculations. The developed solution, leading to the recurrent determination of the probability distribution function for the estimation of the mean value of noise levels and its variance, is shown in this paper.